Computer and creative thinking development : applied theoretical study - Bechta, Hanane (Journal of Human Sciences, 2022)
This study aimed at investigation the relationship between computer use and the development of creative thinking using a range of statistical methods. The results were as follows: - There is a correlation between computer use and the development of creative thinking among university students. - There are statistically significant differences between the average specimen scoring in fluency characteristics attributable to the gender variable and the variable of specialization. - There are statistically significant differences between the average specimens in the flexibility skill due to the gender variable and the variable of specialization. - There are statistically significant differences between the average specimens in the proficiency of the gender variable and the variable of specialization.